Codification of the Natural Resource Legislation in the Russian Empire - NAVASARDOVA, Eleonora Sergeevna; NUTRIKHIN, Roman Vladimirovich; ZINOVYEVA, Tatyana Nikolaevna; SHISHKIN, Vladimir Aleksandrovich; JOLUDEVA, Julia Valeryevna (Journal of Advanced Research in Law and Economics, 2018)
The codification of the legislation on lands, forests, subsoil and other natural resources in the Russian Empire (1721-1917) is studied herein. Some sources of the systematization process in this field of legislation in the period, preceding the formation of the empire, from the time of the ʼCouncil Codeʼ to the reforms of Peter I (1649-1720) are revealed. Initially, the formation of the legal regulation in this field had the form of adoption of numerous separate legal acts. Such law-making methods were casual in nature and resulted in the emergence of internal contradictions in the legislation, which became too extensive and inconsistent. This was the strong reason for the urgent need for its systematization. The land law was most developed in Russia in the pre-imperial and imperial periods, which was due to the prevalence of agricultural production and the special importance of land relations. The land legislation was codified prior to other natural resource industries. The second most important in this area was the forest legislation. This was explained by the abundance of forests and their active use in economic activities, which required serious legal regulation. The importance of subsoil legislation had increased over time, due to increased exploitation of mineral resources. Later, water and faunal law began to develop actively and systematically. The milestone in the development of natural resource industries was M.M. Speransky's codification reform, the main result of which was the appearance of the ʼCode of Laws of the Russian Empireʼ. The separate codes included in it were specifically devoted to land, forest and mineral relations. First of all, they were the ʼCode of Survey Lawsʼ (vol. X), the ʼCode of Institutions and Forest Chartersʼ (vol. VIII) and the ʼCode of Institutions and Mineral Chartersʼ (vol. VII), which, however, were only the part of the array of legal norms on lands, forests and subsoil. Other volumes of the Code of Laws contained a large number of them. The norms of water and faunal law had no separate codes. Their systematization was carried out in the charters of the related branches of law. Along with this codification, a large number of separate normative nature-resource acts were issued. Not all of them were organically included in the relevant codes; they simply joined them as the official annexes. The systematization of the legislation on natural resources in the empire was not very consistent and was not always successful (Engelstein 1993: 339). Even after the most extensive imperial codification, it remained extremely fragmented. However, the demerger of certain natural resource charters from the Code of Laws as the separate codification units indicated the beginning of the formation of the land, forest and mineral law in pre-revolutionary Russia as the independent branches.